Identification of Digestive Tract Endoparasites of Laying Hens in Suruhwadang Village, Kademangan District, Blitar Regency - Mega, Toafan Satrio; Susilowati, Suherni; Hastutiek, Poedji; Kusnoto, Kusnoto; Sunarso, Agus; Witaningrum, Adiana Mutamsari (Journal of Parasite Science, 2024)
This study aims to determine the species, prevalence, and infection degree of endoparasite in the digestive tract of laying hens in Suruhwadang Village, Kademangan District, Blitar Regency. Ninety-six fecal samples were taken from four different farms. Twelve samples of chicken feces aged 20-50 weeks and twelve samples of chicken feces > 50 weeks were taken from each farm. The examinations taken in this study are fecal examinations using native, sediment, and floating methods. The results of identification of digestive tract endoparasites found consisting of Ascaridia galli (68.75%), Heterakis gallinarum (53.12%), Strongyloides avium (5.21%), Trichostrongylus tenuis (6.25%), Eimeria maxima (51,04%), and Eimeria acervulina (3,12%). The highest average degree of worm egg infection was found in layers >50 weeks of age of 373.96 ± 450.41 while the highest average degree of infection of protozoa was found in layers aged >50 weeks of 296,87 ± 600,92. The results of the Chi-Square test showed that there was no significant effect of the difference in the age of laying hens in the layer phase on the prevalence of digestive tract endoparasites, both worm egg and protozoan infections (P>0.05). The results of the Mann-Whitney test showed that there was a significant effect of the difference in the age of the laying hen in the layer phase on the degree of worm egg infection (P<0.05), but the difference in age of the laying hen in the layer phase did not significantly affect the degree of protozoa infection (P>0,05).